The planetary boundary layer over the Arabian Sea during the NE monsoon- A numerical study - LAL, M. (MAUSAM, 1978)
This paper describes the results of numerical simulation of atmospheric boundary layer over Arabian Sea during NE-Monsoon season. A one-dimensional air-sea interaction model was used to simulate the vertical profiles of momentum, heat and moisture fluxes as well as the interface and near-surface meteorological elements which are important in determining the surface layer energy transports. The in simulation experiments were based on initial data obtained from observations made during February-March 1964 over the eastern part of the Arabian Sea. The results demonstrate that the model simulated vertical profiles of temperature and wind are in general agreement with observed structure of the atmospheric boundary layer over Arabian Sea. Comparison with observations of sea surface temperature and near-surface wind and humidity shows that the model is capable of realistic simulations. The model results include the vertical profiles of eddy fluxes of sensible heat, moisture and momentum within the atmospheric boundary layer.